2004
DOI: 10.1111/j.0300-9475.2004.01337.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serum Immunoglobulin E in the Pathogenesis of Plasmodium falciparum Malaria in Ivorian Children

Abstract: The aim of the study was to determine the role of immunoglobulin E (IgE) in the pathogenesis of Plasmodium falciparum malaria in Ivorian children. The study comprised of 90 Ivorian children of both sexes, aged 6-72 months: 30 children suffering from severe malaria, 30 suffering from mild malaria and 30 in good heath (serving as the control population). The children underwent a total serum IgE test for the determination of haemoglobin and platelet level and parasite density. We noted a significant rise in IgE l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 7 publications
1
23
0
2
Order By: Relevance
“…This was supported by a study that showed an association between polymorphisms in FccRIIa, the platelet IgG receptor and disease severity [48]. IgE levels have also been associated with severity of malaria [49] and an increase in IgM levels has also been reported [50]. IgE response to parasites and allergens has been shown to involve an IgE-mediated activation of platelets [51][52][53].…”
Section: Immune Mechanismsmentioning
confidence: 79%
“…This was supported by a study that showed an association between polymorphisms in FccRIIa, the platelet IgG receptor and disease severity [48]. IgE levels have also been associated with severity of malaria [49] and an increase in IgM levels has also been reported [50]. IgE response to parasites and allergens has been shown to involve an IgE-mediated activation of platelets [51][52][53].…”
Section: Immune Mechanismsmentioning
confidence: 79%
“…Are antibodies involved in the observed malaria-induced thrombocytopenia? Most malaria patients with thrombocytopenia possess platelet-associated antibodies that bind to plateletbound malaria antigens [19], and the extent of thrombocytopenia correlates with disease severity and immunoglobulin E (IgE) levels [20]. One hypothesis is that platelet autoantibodies and subsequent phagocytosis by splenic macrophages are responsible for the observed thrombocytopenia, although in experiments with P. berghei in μMT mice (which are considered devoid of functional B cells and IgG antibodies), the mice still develop thrombocytopenia [21].…”
Section: A Spoonful Of Antibodies Makes the Platelets Go Down?mentioning
confidence: 99%
“…20 In other studies, markedly raised levels of IgE were associated with the pathogenesis of severe malaria as IgE containing immune complexes or aggregates were shown to induce TNF-a production by monocytes and other effector cells through cross-linking of CD23 receptors. 21,22 Previous studies observed that the immune system of the pregnant woman is biased towards antibody production and away from cell-mediated immunity. 23,24 It has been suggested that Th2 cytokines (anti-inflammatory cytokines) down regulate Th1 cytokine responses (pro-inflammatory) thus protecting the foetus from rejection 25 but also increasing the incidence of several infectious diseases that are usually under control of CD4 + T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%